A review on fish waste and its derivatives in dye adsorption. - Ladrillo, Aliber Jhon Franco (2023.)
In pursuit of environmental preservation and sustainability, many studies have examined the efficacy of fish waste as an adsorbent for the treatment of dye effluents. This comprehensive review aims to summarize studies related to dye removal using raw, modified and derived fish waste adsorbents and to describe the various factors critical in wastewater application. Several academic databases were searched and 91 research publications were sorted and thoroughly evaluated. Fish scales from local fish markets were mostly used raw material for adsorbent due to its ease of access and availability. Characterization shows that raw fish wastes generally showed non-porous structure. Derived adsorbents from fish wastes revealed to be porous with favorable adsorption capacity. Meanwhile, activated carbons generally have higher adsorption capacity and these were proven from their excellent surface characteristics such as high surface area and rich functional groups. pH of the solution was the key factor in adsorption as it can influence the charge of the adsorbent to strengthen the affinity with dye molecules. Generally, as the initial dye concentration, adsorbent dose and contact time increases, the adsorption capacity also increases. However, at equilibrium, no significant changes are observed at further increase on these parameters. Fish viscera and fish bones from tuna are amongst the top discarded wastes in fish processing industries which can be potential adsorbents for dye removal in wastewaters. As a result, considering its potential and broad availability, it is advised that research employing fish waste to remove various types of dyes be investigated in the Philippines.
Thesis (Undergraduate, Bachelor of Science in Chemical Engineering) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Fish wastes